2005
DOI: 10.2105/ajph.2004.046292
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Life-Course Socioeconomic Position, and Body Weight Trajectories Over 34 years: The Alameda County Study

Abstract: Baltrus et al. | Peer Reviewed | Research and Practice | 1595 RESEARCH AND PRACTICE  Objectives. We investigated whether race differences in weight gain over 34 years were because of socioeconomic position (SEP) and psychosocial and behavioral factors (physical activity, cigarette smoking, alcohol consumption, depression, marital status, number of children). We used a life-course approach to SEP with 4 measures of SEP (childhood SEP, education, occupation, income) and a cumulative measure of SEP.Methods. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 36 publications
(29 reference statements)
9
115
3
Order By: Relevance
“…These are prevalent behaviors, but there is still much to learn about what other feeding behaviors these may be associated with and how these, as a whole, are associated with child overweight. Additionally, the potential association between ethnicity and feeding control may also be reflecting in part a link between maternal overweight, poverty and less controlling reported feeding strategies (Fisher and Birch, 1999;Jain et al, 2001;Wardle et al, 2002), since women from minority backgrounds are more likely to both be overweight (Ogden et al, 2006) and of lower socioeconomic status (Baltrus et al, 2005). Our own sample of African-American women provides some evidence in this regard, with those who shared their homes with a larger number of people being significantly less likely to report the adoption of restrictive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These are prevalent behaviors, but there is still much to learn about what other feeding behaviors these may be associated with and how these, as a whole, are associated with child overweight. Additionally, the potential association between ethnicity and feeding control may also be reflecting in part a link between maternal overweight, poverty and less controlling reported feeding strategies (Fisher and Birch, 1999;Jain et al, 2001;Wardle et al, 2002), since women from minority backgrounds are more likely to both be overweight (Ogden et al, 2006) and of lower socioeconomic status (Baltrus et al, 2005). Our own sample of African-American women provides some evidence in this regard, with those who shared their homes with a larger number of people being significantly less likely to report the adoption of restrictive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The polichoric coefficient correlation between the ordinal variables of education used to compose the scores was 0.426 (participant and father) and 0.465 (participant and mother), showing no redundancy between variables. Previous studies on life course socioeconomic position and health outcomes have established similar scales 25,26 . Scores were categorized as "high" (0-1), "medium" (2), and "low" (3-4), for inclusion in categorical multivariate models.…”
Section: • Uterine Leiomyomamentioning
confidence: 99%
“…This study makes use of a unique opportunity in that it uses information on weight collected over the course of 34 years and includes four measures of SEP; most previous studies were of much shorter duration and only included one or two measures of SEP. Previous analyses of the Alameda County data using these same SEP measures indicated that taken together these measures explained much of the difference in weight gain among African American and white women (13).…”
Section: Introductionmentioning
confidence: 98%